Predictive value of biomarkers in neonatal necrotizing enterocolitis - Liu, Anji; Liang, Ting; Zhang, Rong; Zhao, Shuai; Kang, Lan; Lei, Xiaoping; Dong, Wenbin (Frontiers in Pediatrics, 2025)
Necrotizing enterocolitis (NEC) is an acute, life-threatening intestinal disorder in neonates, associated with notably high mortality. It is characterized by insidious and non-specific early clinical manifestations, a rapid disease progression course, and often results in long-term sequelae in affected infants, such as short bowel syndrome and neurodevelopmental impairments. The pathogenesis of NEC remains complex and not fully elucidated; thus, the screening and validation of biomarkers with high specificity, high sensitivity, and clinical applicability constitutes a core strategy to enhance the efficacy of early diagnosis and accuracy of prognostic assessment for this disease. This article aims to systematically synthesize the current clinical dilemmas in the field of NEC and the update status of relevant clinical guidelines, with a focus on reviewing the research advances of both traditional and emerging biomarkers in the contexts of NEC early diagnosis, disease staging, severity stratification, prediction of surgical intervention requirements, and prognostic evaluation. Additionally, it analyzes the consistencies and discrepancies between cutting-edge research findings and clinical guidelines, and prospects the future development direction of precision diagnosis and treatment for NEC.